Prototipe Alat Penghancur dan Pengepres Sampah Plastik Otomatis Berbasis Arduino Skala Laboratorium - Ronauli Hutabarat; Muhammad Gabriel; Ocsirendi; Enggar Hero Istoto (Jurusan Teknik Elektro Fakultas Teknik Universitas Bangka Belitung, 2026)
Plastic waste poses a significant environmental challenge, particularly in the Bangka Belitung Islands, Indonesia, where Sungailiat receives approximately 68 tons of waste per day. This study presents the development of an automatic plastic waste management prototype that utilizes an Arduino-based control system to address this issue. The system integrates shredding blades driven by a 24 V wiper motor with pneumatic cylinder compression, which is controlled through a network of sensors. The prototype employs a proximity sensor to detect waste at a distance of 1–5 cm, while ultrasonic sensor 1 monitors the shredding chamber at a distance of 5–25 cm to automatically activate the shredding motor. Furthermore, ultrasonic sensor 2 detects the accumulation of shredded plastic in the compression chamber at a distance of 5–10 cm, triggering the pneumatic cylinder for automatic compression. The testing was focused on PET (Polyethylene Terephthalate) plastic waste, demonstrating successful automatic shredding performance; however, the resulting shredded material remained coarse with non-uniform particle sizes. Nevertheless, the compression results after 5–10 minutes were not optimal, producing blocks with insufficient compaction that were easily broken. This indicates the need for further optimization of heater positioning and compression pressure to produce denser plastic blocks for efficient recycling processes. The novelty of this research lies in the integration of shredding and pressing systems into a single Arduino-based automatic prototype that operates sequentially using proximity and ultrasonic sensors, thereby improving the efficiency of plastic waste processing at the laboratory scale